2016
DOI: 10.1161/circresaha.115.307918
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for Telomerase in the Mechanism of Flow-Mediated Dilation in the Human Microcirculation

Abstract: Not all of the effects of telomerase can be easily explained by its nuclear actions. Growing evidence suggests that TERT, the catalytic subunit of telomerase, can reversibly translocate from the nucleus to organelles (including the mitochondria), in a dose-and time-dependent manner, in response to stressors, Objective: We examined the hypothesis that telomerase activity modulates microvascular flow-mediated dilation, and loss of telomerase activity contributes to the change of mediator from nitric oxide to mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
119
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 67 publications
6
119
1
2
Order By: Relevance
“…The same is true for selective deletion of endothelial SOD, which leads to increased oxidative stress and reduced endotheliumdependent, NO-mediated relaxations. The exaggerated reduction in NO bioavailability caused by ROS can be alleviated experimentally by (1) inhibiting the activation of endothelial cell membrane transforming growth factor-β 154 and endoplasmic reticulum membrane TLR9 receptors 155 thereby reducing the expression of NOX and cyclooxygenase-2; (2) augmenting (eg, with the administration of adiponectin, capsaicin, or glucagon-like peptide-1; see Other Hormones and Circulating Mediators section of this article) the intracellular concentration of cAMP to activate PKA that increases uncoupling protein 2 in the mitochondria and cAMP-responsive element-binding protein in the nucleus, boosting the expression of the antioxidant enzymes mitochondrial complex I and HO-1, respectively; (3) stimulating AMPK (eg, by augmenting the production of adiponectin) to activate nuclear factor-erythroid 2-related factor-2 and thus stimulates HO-1 gene transcription; (4) reducing ROS production and DNA release in the mitochondria (by activating telomerase and increasing the presence of its catalytic subunit 156 ); and (5) by the exogenous administration of epigallocatechins, 157 erythropoietin, 112 ghrelin, 158 estrogens, 89 or other antioxidants. 15,92,120 Part of the improvement of endothelium-dependent relaxations caused by HO-1 induction or exogenous antioxidants can be attributed to restoration of the gatekeeper role of NO in preventing endothelium-dependent contractions.…”
Section: Reduced No Bioavailabilitymentioning
confidence: 99%
“…The same is true for selective deletion of endothelial SOD, which leads to increased oxidative stress and reduced endotheliumdependent, NO-mediated relaxations. The exaggerated reduction in NO bioavailability caused by ROS can be alleviated experimentally by (1) inhibiting the activation of endothelial cell membrane transforming growth factor-β 154 and endoplasmic reticulum membrane TLR9 receptors 155 thereby reducing the expression of NOX and cyclooxygenase-2; (2) augmenting (eg, with the administration of adiponectin, capsaicin, or glucagon-like peptide-1; see Other Hormones and Circulating Mediators section of this article) the intracellular concentration of cAMP to activate PKA that increases uncoupling protein 2 in the mitochondria and cAMP-responsive element-binding protein in the nucleus, boosting the expression of the antioxidant enzymes mitochondrial complex I and HO-1, respectively; (3) stimulating AMPK (eg, by augmenting the production of adiponectin) to activate nuclear factor-erythroid 2-related factor-2 and thus stimulates HO-1 gene transcription; (4) reducing ROS production and DNA release in the mitochondria (by activating telomerase and increasing the presence of its catalytic subunit 156 ); and (5) by the exogenous administration of epigallocatechins, 157 erythropoietin, 112 ghrelin, 158 estrogens, 89 or other antioxidants. 15,92,120 Part of the improvement of endothelium-dependent relaxations caused by HO-1 induction or exogenous antioxidants can be attributed to restoration of the gatekeeper role of NO in preventing endothelium-dependent contractions.…”
Section: Reduced No Bioavailabilitymentioning
confidence: 99%
“…Many studies have also demonstrated that acute activation of telomerase using AGS-499 restored NO bioavailability and limited ROS production in micro-vessels from subjects with CAD. (153) …”
Section: Telomerase As a Therapeutic Target In Cardiovascular Diseasementioning
confidence: 99%
“…In the current issue of Circulation Research, Beyer et al 7 build on this conceptual thread pursuing a unique line of inquiry in the resistance vasculature. Could telomerase, or more specifically TERT, regulate arterial tone by localizing to mitochondria and influencing the production of reactive oxygen species?…”
Section: Article See P 856mentioning
confidence: 99%